Conflitos e trocas culturais em Relato de um certo Oriente e Dois irmãos, de Milton Hatoum - Pereira, Marcos Douglas Bourscheid (2019)
The present thesis concentrates on the comparative analysis between the novels Tale of a certain Orient (1989) and The brothers (2000), by Milton Hatoum. It was intended to compare the cultural and social influences on the ethnic mosaic that constitutes the population of Manaus, with special emphasis on the Lebanese immigrants and their relationship with the indigenous, as this is one of the main themes of the works under analysis. As a principal basis for this study, the theoretical support of Paul Ricoeur (1994); Homi Bhabha (1998); Gilberto Freyre (2004 e 2015); Maria da Luz Pinheiro de Cristo (2007); Edward Said (2016); e Georges Bataille (2017), among others. The analysis focuses on the behavior of the characters of two families of Lebanese origin in which, in the new cultural context, the parents lost control over some of their children. Amid the disputes and changes in the model of child rearing, the parents, originating in a culture still strongly patriarchal, are supplanted by the mothers who become the matriarchs of the family. In assuming the reins of the family, such matriarchs, due to excessive love and permissive behavior towards their children, contribute to family decadence. Thus, the present thesis focuses on migratory issues, social violence, cultural clashes and the formation of the family of Lebanese and their descendants in Manaus, as well as the clash between this culture and that of the indigenous, cruelly exploited in the works in analyze. All these questions point to the fragmentation of social relations and the subject in contemporary society.